Development of Science Comic Based on Auvidi Media on Global Warming Materials - Novita Tri Wulan Sari; Dwi Bagus Rendy Astid Putera; Ana Yuniasti Retno Wulandari; Nur Qomaria; Yamin Yamin (Journal of Education and Learning Research, 2025)
Science comic based on auvidi media are rarely applied in science learning. Based on the result of pre-research at SMP Al Hikam Kemayoran students consider that learning science is very difficult and boring due to the lack of use of learning media. The solution given is to develop science comics based on auvidi media on global warming materials. This development research aims to determine the feasibility, readability, and students responses to the media. This study uses the ADDIE development model. This research was conducted at SMP Al Hikam Kemayoran class VII with 34 students. The sampling method is a saturated sample technique for class VII students. Data collection techniques use interviews, quesrionnaires, and documentation. The results of the media feasibility validation obtained an average result of 0,98, while the material eligibility validation obtained an average of 0,83 as very valid. The readability percentage obtained an average score 83,50% and student respons obtained an average score of 88,88% in the very good category.